2016
DOI: 10.1007/s10570-016-0979-x
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationships between cellulase activity and cellulose particle morphology

Abstract: It is well documented that the enzymatic hydrolysis of cellulose follows a reaction pattern where an initial phase of relatively high activity is followed by a gradual slow-down over the entire course of the reaction. This phenomenon is not readily explained by conventional factors like substrate depletion, product inhibition or enzyme instability. It has been suggested that the underlying reason for the loss of enzyme activity is connected to the heterogeneous structure of cellulose, but so far attempts to es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…Furthermore, neither depletion of surface area nor shortening of chains explains long term hydrolysis slowdown 8 . Previous studies have linked structural effects of enzyme degradation to accessibility 41,42,48,[52][53][54][55] , but to our knowledge, the results shown here are the first specifically quantifying the accessibility of cellulose by means of productive binding capacity measurements throughout the duration of hydrolysis.…”
Section: Product]mentioning
confidence: 92%
“…Furthermore, neither depletion of surface area nor shortening of chains explains long term hydrolysis slowdown 8 . Previous studies have linked structural effects of enzyme degradation to accessibility 41,42,48,[52][53][54][55] , but to our knowledge, the results shown here are the first specifically quantifying the accessibility of cellulose by means of productive binding capacity measurements throughout the duration of hydrolysis.…”
Section: Product]mentioning
confidence: 92%
“…All experiments were performed in 50 mM NaAcetate pH 5.0 at 25°C and Avicel (PH101, Sigma Aldrich 11365), that had initially been washed and precipitated five times in buffer, was used as substrate. Avicel consists of microcrystalline cellulose, and the product used here has a typical particle size of 10-50 µm [23]. The quenched flow instruments works better with smaller particles, and the substrate used here was dispersed for 10 min with an ultra Turrax T25 Basic (IKA, Staufen, Germany) coaxial homogenizer with a nominal final particle size of 5 µm.…”
Section: Enzymes and Substratementioning
confidence: 99%
“…microcrystalline-and amorphous cellulose [55,56]. Avicel particles have a complex structure with a high degree of roughness [23], which probably present a diversity of attack sites for the enzymes.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Bansal et al [3] performed a systematic study and found that approximately 90% of the cause of rate retardation was due to substrate depletion, accessibility, and “hydrolysability” (propensity of cellulose to be hydrolyzed by enzymes), while the intrinsic reactivity remained effectively unchanged. Olsen et al [21] found a correlation between hydrolysis rate and surface area (and roughness) of cellulose particles, which decrease with the extent of conversion.…”
Section: Introductionmentioning
confidence: 99%